2010
DOI: 10.3109/08820131003615498
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of T Helper Subsets in the Pathogenesis of Asthma

Abstract: The cardinal features of asthma include pulmonary inflammation and airway hyperresponsiveness (AHR). Classically, asthma, specifically allergic asthma, has been attributed to a hyperactive Th2 cell immune response. However, the Th2 cell-mediated inflammation model has failed to adequately explain many of the clinical and molecular aspects of asthma. In addition, the outcomes of Th2-targeted therapeutic trials have been disappointing. Thus, asthma is now believed to be a complex and heterogeneous disorder, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
90
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 135 publications
(152 reference statements)
0
90
1
2
Order By: Relevance
“…Each of these cell types has defined roles in asthma (17)(18)(19)(20). To determine whether Ova treatment of Mfge8 −/− mice affected T-cell differentiation, we isolated lymphocytes from the lung and measured cytokine production (or expression of FoxP3 for Treg cells).…”
Section: Resultsmentioning
confidence: 99%
“…Each of these cell types has defined roles in asthma (17)(18)(19)(20). To determine whether Ova treatment of Mfge8 −/− mice affected T-cell differentiation, we isolated lymphocytes from the lung and measured cytokine production (or expression of FoxP3 for Treg cells).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with asthma typically suffer from chronic bronchial hyperresponsiveness, overproduction of mucus, allergen-specific IgE expression, and airway remodeling (2,3). Allergic airway inflammation is characterized by an infiltrate of eosinophils, neutrophils, and Th2 and Th17 lymphocytes expressing interleukin-4 (IL-4), IL-5 IL-13, and IL-17 (4).…”
mentioning
confidence: 99%
“…1 T helper cells play a pivotal role in the pathogenesis of asthma (1)(2)(3)(4). CD4 1 T helper cell subsets, which include T helper cell type 1 (Th1), Th2, and Th17 cells, are key components of the adaptive immune response in rodents and humans (1,(5)(6)(7).…”
mentioning
confidence: 99%
“…CD4 1 T helper cell subsets, which include T helper cell type 1 (Th1), Th2, and Th17 cells, are key components of the adaptive immune response in rodents and humans (1,(5)(6)(7). Allergic responses in the lung are traditionally thought of as being Th2 mediated; however, recent studies have shown that IL-9 contributes to allergic responses by promoting mast cell expansion and production of IL-13, which stimulates the release of mucus and contributes to airway hyperresponsiveness (1,5,8,9). Serum IL-9 levels, which correlate with symptom severity in patients with allergic rhinitis, depend on exposure to a causal allergen (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%